Histological and Immunohistochemical Evaluation of the Efficacy of a New Cosmetic Formulation in the Treatment of Skin Photoaging - M. T. Truchuelo; N. Jiménez; L. Miguel-Gomez; A. Hermosa; N. Sánchez-Neila; J. Cuevas (Dermatology Research and Practice)
Objective. Mechanism of action of cosmetic products is not often studied. The aim of this study is to determine the histological, immunohistochemical, and clinical changes of a new cosmetic formulation. Methods. Prospective, single-blind, patient-controlled, randomized study in 10 volunteers with mild to moderate skin photoaging on the back of their hands. The product was applied on one hand and a standard cream on the other hand, twice a day for three months. Standardized photographs were taken on basal (T0) and final visit (T1) and skin biopsies were performed. Changes on histological and immunohistochemical markers were studied. Subjective clinical changes were determined. Results. After treatment, a 26.3% improvement on epidermal thickness was detected and a significant increase on collagens I and III, elastin, and fibronectin fibers was achieved (p<0.05). As the expression of MMPs remained stable, this improvement of dermal matrix was attributed to the stimulation of their synthesis. A significant clinical improvement on the treated hand was obtained, compared to control hand. Conclusion. This new cosmetic product with combination of three registered technologies (IFC-CAF, WGC, and RetinSphere), focused on regenerating dermal matrix and activating proliferation of skin cells, has shown to be efficient in the reversion of skin photoaging.